2010
DOI: 10.1128/jb.00383-10
|View full text |Cite
|
Sign up to set email alerts
|

The MerR/NmlR Family Transcription Factor of Streptococcus pneumoniae Responds to Carbonyl Stress and Modulates Hydrogen Peroxide Production

Abstract: The NmlR sp transcription factor of Streptococcus pneumoniae is shown to induce adhC (alcohol dehydrogenase) expression in the presence of both formaldehyde and methylglyoxal. nmlR sp and adhC mutant strains display altered and opposite aerobic growth phenotypes. The nmlR sp strain exhibits increased resistance to high oxygen tension, attributable to decreased H 2 O 2 production, which correlated with downregulation of carbamoyl phosphate synthase (carB). This indicates a possible role for AdhC in aldehyde met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 21 publications
2
32
0
Order By: Relevance
“…Many predicted mRNA targets found in this study also encode proteins that contribute to radiation survival, such as RecA, RuvA, and RadA (33,39,70). Other mRNAs do not encode proteins directly associated with DNA repair but are associated with stress response mechanisms or global gene regulation, such as the TetR family transcriptional regulator DR_0074, the cyclic AMP receptor protein (CRP)/ferredoxin-NADP ϩ reductase (FNR) family transcriptional regulator DR_ 0097, and the MerR family transcriptional regulator (71)(72)(73). geothermalis.…”
Section: Discussionmentioning
confidence: 99%
“…Many predicted mRNA targets found in this study also encode proteins that contribute to radiation survival, such as RecA, RuvA, and RadA (33,39,70). Other mRNAs do not encode proteins directly associated with DNA repair but are associated with stress response mechanisms or global gene regulation, such as the TetR family transcriptional regulator DR_0074, the cyclic AMP receptor protein (CRP)/ferredoxin-NADP ϩ reductase (FNR) family transcriptional regulator DR_ 0097, and the MerR family transcriptional regulator (71)(72)(73). geothermalis.…”
Section: Discussionmentioning
confidence: 99%
“…As this organism lacks proteins that have been shown to protect against oxidative stress (e.g., catalase) (10), several studies focused on pneumococcal H 2 O 2 resistance (34,37,42). This resistance is important not only for the oxidative stress response of the pathogen but also for pneumococcal physiology (7,36) and pneumococcal interactions with other bacteria (24,33,40) and the host (12,13,35). Although it had been speculated that tpxD (psaD) encodes a pneumococcal thiol peroxidase, this is the first report that established the identity of the protein by direct enzymatic assays, demonstrated its mechanism of action, and showed that TpxD expression is regulated in response to H 2 O 2 levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, all mutants had survival rates similar to that of the wild-type strain following paraquat and low-pH exposure. Also, the pneumococcus might employ polyamine-mediated defence mechanisms to overcome nitrosative stress during infection, as described for E. coli via the merR transcriptional regulator (Bower et al, 2009;Potter et al, 2010). Thus, subtle perturbations in intracellular polyamine levels may not significantly affect pneumococcal stress responses in vitro.…”
Section: Role Of Polyamines In Pneumococcal Diseasementioning
confidence: 99%